Digital marketing and sales technologies: big data and synergy effect - V. Ya. Konks (Publishing House of the State University of Management, 2019)
Currently, many Russian companies successfully solve the problem of attracting a significant number of customer requirements and requests for sales and service. As a result, there is a problem of matching the company’s capabilities to meet the declared services and their level, reserving excess capacity and resources of the company, which leads to a decrease in profits. The article is based on the queuing theory and considers the application of new ways to measure, achieve and maintain the efficiency of the business, leading to an increase in its elasticity and maneuverability, as the efficiency of the business is measured by comparing the collected data, existing indicators, balance sheets or key performance indicators.